A Framework for Assessing the Vulnerability of Communities in the Canadian Arctic to Risks Associated with Climate Change - Ford, J.D.; Smit, B. (ARCTIC, 2004)
Adaptation to climate change is recognized as an important policy issue by international bodies such as the United Nations and by various national governments. Initiatives to identify adaptation needs and to improve adaptive capacity increasingly start with an assessment of the vulnerability of the system of interest, in terms of who and what are vulnerable, to what stresses, in what way, and what capacity exists to adapt to changing risks. Notwithstanding the scholarship on climate change itself, there are few studies on the nature of Arctic communities' vulnerability to climate-change risks. We review existing literature on implications of climate change for Arctic communities, develop a conceptual model of vulnerability, and present an analytical approach to assessing climate hazards and coping strategies in Arctic communities. Vulnerability is conceptualized as a function of exposure to climatic stresses and the adaptive capacity to cope with these stresses. The analytical framework employs place-specific case studies involving community residents and integrates information from multiple sources, both to document current exposures and adaptations and to characterize future exposures and adaptive capacity. L'adaptation au changement climatique est perçue comme un enjeu crucial par les organes internationaux tels que les Nations unies et plusieurs gouvernements nationaux. Des initiatives visant l'identification des besoins en matière d'adaptation, ainsi que l'amélioration de la capacité adaptative, débutent de plus en plus par un bilan de la vulnérabilité du système en cause, c'est-à-dire qui et quoi est vulnérable à quels stress et de quelle manière, et quelle capacité existe pour une adaptation aux risques changeants. Malgré les travaux de recherche sur le changement climatique même, il n'existe que peu d'études sur la nature de la vulnérabilité des communautés arctiques aux risques découlant du changement climatique. On passe en revue la documentation qui existe sur les implications que représente le ...